2020
DOI: 10.1093/jxb/eraa066
|View full text |Cite
|
Sign up to set email alerts
|

Macroalgal–bacterial interactions: identification and role of thallusin in morphogenesis of the seaweed Ulva (Chlorophyta)

Abstract: Macroalgal microbiomes have core functions related to biofilm formation, growth, and morphogenesis of seaweeds. In particular, the growth and development of the sea lettuce Ulva spp. (Chlorophyta) depend on bacteria releasing morphogenetic compounds. Under axenic conditions, the macroalga Ulva mutabilis develops a callus-like phenotype with cell wall protrusions. However, co-culturing with Roseovarius sp. (MS2) and Maribacter sp. (MS6), which produce various stimulatory chemical mediators, completely recovers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 44 publications
1
59
0
7
Order By: Relevance
“…are of high relevance in macroalgal aquaculture despite their low relative abundances of 0.08, 0.3, and 1.2% in rearing water. Indeed, previous studies highlighted their importance in the morphological development of germlings of U. mutabilis, U. intestinalis, and U. linza (Grueneberg et al, 2016;Ghaderiardakani et al, 2017;Weiss et al, 2017a) through the release of morphogens, such as thallusin, at low concentrations in the fg/ml range, but with high biological activity, that trigger algal growth and morphogenesis (Matsuo et al, 2005;Wichard, 2015;Alsufyani et al, 2020). As we did not test the bioactivity of the bacteria, other unknown taxa adapted to the aquaculture environment might also induce Ulva's morphogenesis.…”
Section: The Potential Role Of Different Bacterial Taxa In Cross-kingmentioning
confidence: 99%
“…are of high relevance in macroalgal aquaculture despite their low relative abundances of 0.08, 0.3, and 1.2% in rearing water. Indeed, previous studies highlighted their importance in the morphological development of germlings of U. mutabilis, U. intestinalis, and U. linza (Grueneberg et al, 2016;Ghaderiardakani et al, 2017;Weiss et al, 2017a) through the release of morphogens, such as thallusin, at low concentrations in the fg/ml range, but with high biological activity, that trigger algal growth and morphogenesis (Matsuo et al, 2005;Wichard, 2015;Alsufyani et al, 2020). As we did not test the bioactivity of the bacteria, other unknown taxa adapted to the aquaculture environment might also induce Ulva's morphogenesis.…”
Section: The Potential Role Of Different Bacterial Taxa In Cross-kingmentioning
confidence: 99%
“…The genus is best known for its broad distribution in marine (fully saline), brackish, and freshwater ecosystems in tropical, temperate, and the less-studied polar regions ( Figure 1A). A genetic toolbox was developed, and essential chemical mediators of the algae-bacteria interaction were identified (Joint et al, 2002;Tait et al, 2009;Oertel et al, 2015;De Clerck et al, 2018;Alsufyani et al, 2020).…”
Section: Macroalgae and Bacteria Team Up To Adapt To Changing Ecosystemsmentioning
confidence: 99%
“…Bacteria can be associated with the surface, the holdfast, or the chemical boundary layer of the alga in the surrounding water (Mieszkin et al, 2013;Egan et al, 2014;Wichard, 2015). Based on different scenarios, chemical compounds produced on macroalgal surface or its vicinity may present the primary factors driving the dynamic of bacterial communities within the network of algae-bacteria interactions (Lachnit et al, 2013;Kessler et al, 2018;Alsufyani et al, 2020;Burgunter-Delamare et al, 2020;Paix et al, 2020). Employing a multi-omics approach on the thallus scale demonstrated that chemical production, which is mostly stimulated by the algal physiology, defines the microbial community structure and composition at the surface of individual thalli of Taonia atomaria.…”
Section: Chemically-mediated Bacterial-macroalgal Interactionsmentioning
confidence: 99%
See 2 more Smart Citations